Acinic cell carcinoma of the oral and maxillofacial region: an international multicenter study - Laura Borges KIRSCHNICK; Felipe Martins SILVEIRA; Lauren Frenzel SCHUCH; Ana Carolina Uchoa VASCONCELOS; Ana Paula GOMES; Jean Nunes dos SANTOS; Dandara Andrade SANTANA; Felipe Paiva FONSECA; Ricardo Alves MESQUITA; Elismauro Francisco de MENDONÇA; Sebastião Silvério SOUSA-NETO; Hélder Antônio Rebelo PONTES; et al. (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The aim of this study was to describe the prevalence, clinicopathological, and prognostic features of acinic cell carcinoma (AciCC) of the oral and maxillofacial region. AciCC cases were retrospectively retrieved from 11 pathology centers of three different countries. Medical records were examined to extract demographic, clinical, pathologic, and follow-up information. A total of 75 cases were included. Females (65.33%) with a mean age of 45.51 years were mostly affected. The lesions usually presented as an asymptomatic (64.28%) nodule (95.66%) in the parotid gland (70.68%). The association of two histopathological patterns was the most common finding (48.93%) and the tumors presented mainly conventional histopathological grades (86.11%). Surgical treatment was performed in the majority of the cases (59.19%). Local recurrence was observed in 20% of the informed cases, regional metastasis in 30.43%, and distant metastasis in 12.50%. The statistical analysis showed that the cases with a solid histopathological pattern (p=0.01), high-grade transformation (p=0.008), recurrence (p=0.007), and regional metastasis (p=0.03) were associated with poor survival. In conclusion, high histopathological transformation, presence of nodal metastasis, and recurrence were prognostic factors for AciCC of the oral and maxillofacial region.